The Influence of Demographic Characteristics and Financial Literacy on Investor Behavioral Biases - Tjoputri, R. Shinta Amelia; Murhadi, Werner R.; Marciano, Deddy (Universitas Muhammadiyah Yogyakarta, 2025)
This study examines the impact of financial literacy variables and demographic characteristics on investor behavioral biases. The behavioral biases used in this study are overconfidence, disposition effect, herding bias, and mental accounting. Demographic variables include gender, age, education level, employment status, income level, and investment experience. This study used the SEM method. The results of this study indicate that herding bias, disposition effect, and overconfidence are all significantly influenced by gender. Overconfidence, disposition effect, herding bias, and mental accounting are not significantly influenced by occupation, income level, or investment experience. Overconfidence, disposition effect, herding bias, and mental accounting are all significantly influenced by financial literacy. This study fills a gap in the literature by highlighting how demographic factors and financial literacy can influence investor behavioral biases. This study suggests that gender may influence overconfidence, the disposition effect, and ordinary herding. The results indicate that age influences the level of overconfidence and the disposition effect in investors. Therefore, older investors tend to be more overconfident. The older investors are, the more aware they are of investment losses, preventing them from experiencing the disposition effect. This study also demonstrates that good financial literacy can reduce investor bias in investment decisions.